PENGARUH BIAYA R&D BIAYA IKLAN TERHADAP KINERJA LABA - Kusmawati (Jurnal Keuangan dan Bisnis, 2020)
The main firm’s goal according to theory of the firm is to increase owners’ by increasing theperformance of profit. The performance of profit the firm can be influenced by many factors,among them research and development intensity and advertising intensity. The purpose ofthis study was to obtain empirical evidence of the effect of R&D and advertising expense toto performance of profit. The population used in this study is manufacture company inIndonesian stock exchange during the period 2016-2018. The sampling technique usingpurposive sampling method and obtained sample 48 of manufacture company. The methodused is quantitative research method. For the method of data analysis using multiple linearregression analysis. As for data processing using IBM SPSS 23.0 The results showed R&Dexpense didnt have affect on performance of profit. Whereas advertising expensehave affecton performance of profit